Fabrication of glutathione-modified gold nanoparticles as 3-chloropropane-1,2-diol sensor - Faramitha, Yora; Barori, Fadhlurrahman Rafi; Dimawarnita, Firda; Siswanto; Aqoma, Havid; Nugraha, Adam F; Ferdiansyah, Alfian (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2023)
Refined palm oil products may contain a harmful substance called as 3-monochloropropane-1,2-diol (3-MCPD), which can potentially be carcinogenic if consumed in excess. The determination of 3-MCPD depends on the sophisticated machine and highly skilled technicians but it is time-consuming. A simple method that proposes rapid detection remains a challenge. Hence, this research aims to develop a colorimetric-based rapid detection sensor using gold nanoparticles functionalized with a ligand, glutathione (GSH) to be bound to 3-MCPD. Varied concentrations of GSH were evaluated to obtain stable GSH-AuNPs. The characterization results showed that the composition of the stable GSH-AuNPs has been achieved by 250 µL of 0.02 M GSH addition. A stable GSH-AuNPs was ruby red with surface plasmon resonance (SPR) band at 520 nm and an average nanoparticle size of 30 nm. The indication for detection of 3-MCPD was marked by the decrease in the absorbance intensity. Thus, GSH-AuNPs have potential to be developed for the 3-MCPD sensor application.